2003
DOI: 10.1152/ajprenal.00388.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salt on hypertension and oxidative stress in a rat model of diet-induced obesity

Abstract: . Effect of salt on hypertension and oxidative stress in a rat model of diet-induced obesity. Am J Physiol Renal Physiol 285: F619-F628, 2003. First published June 10, 2003 10.1152 10. /ajprenal.00388. 2002 diet is known to induce or aggravate hypertension in animal models of hypertension and in humans. When Sprague-Dawley rats (n ϭ 60) are fed a moderately high-fat diet (32% kcal fat, 0.8% NaCl) for 10 wk, about one-half develop obesity [obesity prone (OP)] and mild hypertension, whereas the other half [obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
78
4
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 55 publications
8
78
4
2
Order By: Relevance
“…31,32 Second, independent of energy intake, chronic salt overload induced adipocyte hypertrophy and increased mass of adipose depots and high plasma leptin concentration by enhancing the adipocyte insulin sensitivity for glucose uptake, the insulin-induced glucose metabolism, and lipogenic capacity of white adipose tissue in rats. 1,2,33 We also found that sodium intake was positively and independently associated with increased circulating levels of leptin. Leptin is one of the most important adipokines secreted by fat cells, with a variety of physiologic roles related to the control of metabolism, maintenance of energy homeostasis and body weight, inflammatory response, and urinary sodium excretion.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…31,32 Second, independent of energy intake, chronic salt overload induced adipocyte hypertrophy and increased mass of adipose depots and high plasma leptin concentration by enhancing the adipocyte insulin sensitivity for glucose uptake, the insulin-induced glucose metabolism, and lipogenic capacity of white adipose tissue in rats. 1,2,33 We also found that sodium intake was positively and independently associated with increased circulating levels of leptin. Leptin is one of the most important adipokines secreted by fat cells, with a variety of physiologic roles related to the control of metabolism, maintenance of energy homeostasis and body weight, inflammatory response, and urinary sodium excretion.…”
Section: Discussionsupporting
confidence: 55%
“…For instance, animal studies have shown that a high sodium diet increases adipose tissue mass and adipocyte size, and leptin production. 1,2 In humans, greater sodium consumption has been linked to higher body weight, 3,4 possibly due to sodium' s effect on fluid intake because high sodium intake is often accompanied by high consumption of energy-dense foods and sugarsweetened soft drinks. [5][6][7][8][9] However, this may not always be the case because other studies have reported a positive relationship between dietary sodium intake and obesity independent of energy intake and sugar-sweetened beverage consumption.…”
mentioning
confidence: 99%
“…Oxidative stress develops when the well-regulated balance between prooxidants and antioxidants becomes uncontrolled and tips in favor of pro-oxidants. Oxidative stress is a major contributor to the aging process (26) and appears to be a common feature of hypertensive disorders from diverse origins (9,(27)(28)(29). ROS have also been shown to be involved in cardiac hypertrophy induced by several stimuli, such as mechanical stretch, endothelin and angiotensin II (30).…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] However, we found that MC4R (Ϫ/Ϫ) mice, which have most of the characteristics of the metabolic syndrome, including obesity, visceral adiposity, hyperleptinemia, and hyperinsulinemia, do not develop hypertension when fed an NSD or HSD. Moreover, arterial pressure in MC4R (Ϫ/Ϫ) mice failed to increase in response to an HSD despite Ϸ40% greater sodium intake (resulting from hyperphagia) when compared with WT mice.…”
Section: Effect Of Hsd (4% Nacl) On Cardiovascular Function In Mc4r (mentioning
confidence: 99%